2016
DOI: 10.1080/15389588.2016.1198008
|View full text |Cite
|
Sign up to set email alerts
|

Driving self-regulation and ride service utilization in a multicommunity, multistate sample of U.S. older adults

Abstract: Objectives: This study examined a multicommunity alternative transportation program available 24 hours a day, 7 days a week, for any purpose, offering door-through-door service in private automobiles to members who either do not drive or are transitioning away from driving. Specific aims were to describe the characteristics of members by driving status and ride service usage of these members. Methods: Data came from administrative records maintained by a nonprofit ride service program and include 2,661 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Only among the 80+ cohort within Rural and Urban non-Dublin was its dominance replaced by being Driven by someone else. These data clearly demonstrate that older Irish adults rely upon driving oneself as their most popular form of transport and given the benefits of this it is important to ensure that access to driving is not unnecessarily hindered, e.g., by unwarranted medical screening of older drivers (O’Neill, 2012), while facilitating access to alternative transportation using private or hired cars such as through the creative ITNAmerica system (Bird et al, 2017). With the increase in the level of automation within cars, driving may increasingly become easier and safer making it arguably even more attractive to older people (Harper et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Only among the 80+ cohort within Rural and Urban non-Dublin was its dominance replaced by being Driven by someone else. These data clearly demonstrate that older Irish adults rely upon driving oneself as their most popular form of transport and given the benefits of this it is important to ensure that access to driving is not unnecessarily hindered, e.g., by unwarranted medical screening of older drivers (O’Neill, 2012), while facilitating access to alternative transportation using private or hired cars such as through the creative ITNAmerica system (Bird et al, 2017). With the increase in the level of automation within cars, driving may increasingly become easier and safer making it arguably even more attractive to older people (Harper et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…In Japan, the government has implemented a program for the voluntary return of driver’s licenses by older drivers and offers certain compensation to encourage voluntary participation [28]. However, most older drivers reported that they want to continue driving a private car instead of using public transportation, because they consider trains, subways, and buses to be inconvenient and misaligned with their travel needs, and taxis to be unsafe and too expensive [29]. In both rural and suburban areas, there is a lack of good public transportation options for the elderly even if they want to use them.…”
Section: Discussionmentioning
confidence: 99%
“…It could be demonstrated that older adults are willing to use, if available, alternative transportation possibilities. This has been predominantly described in older women [12]. In contrast to elderly drivers below age 70, the number of older drivers decreases with higher comorbidity levels, which underlines the ability of self-regulation [14].…”
Section: Review Thiemementioning
confidence: 98%
“…Additionally, due to general frailty in older age, injuries caused by car accidents are more severe, which potentially balloons the existing impact of age-related changes of driving capability [11]. Recent studies suggest that most older drivers responsibly evaluate their driving capabilities and stop driving in case of health care utilization, use of relevant medication and specific medical conditions [12,13]. It could be demonstrated that older adults are willing to use, if available, alternative transportation possibilities.…”
Section: Review Thiemementioning
confidence: 99%